Primary yolk sac tumour of the liver in adulthood. - Wong, N A (1998)
Primary yolk sac tumour of the liver is exceedingly rare. A 28 year old woman presented with a cystic liver mass and a markedly raised serum alpha-fetoprotein concentration. She underwent a partial hepatectomy for a suspected hepatocellular carcinoma but histological examination of the tumour revealed the classical morphological and immunohistochemical features of a yolk sac tumour. There was no evidence of an extrahepatic primary source. Review of this case, together with the six previously reported adult cases of primary yolk sac tumours of the liver, revealed several features of the tumour that may aid differentiation from hepatocellular carcinoma, with potential therapeutic implications.